Illegal Fintech P2P Lending in Indonesia: Addressing the Problem of Over-Indebtedness During the COVID-19 Pandemic - Nur Hadiyati (Muhammadiyah University Press, 2021)
Objective: This study aims to examine and analyze the problem of over-indebtedness in illegal Fintech P2P Lending during the COVID-19 pandemic. Methodology: This research uses doctrinal law research. This doctrinal research is descriptive analytical which aims to examine and explain the problems studied. The data used is secondary data and then analyzed using qualitative analysis techniques to get the correct conclusion. Finding: In the economic sector, the challenges of the COVID-19 pandemic require various groups, especially Fintech P2P Lending providers, to respond to changes in an integrated and comprehensive manner, so that these challenges can be managed into opportunities. This research shows the rampant risk of “over-indebtedness” due to people’s economic conditions, lack of financial literacy, unexpected events during the COVID-19 pandemic, and the presence of illegal Fintech P2P Lending as predatory lending. There needs to be preventive efforts to reduce the risk of “over-indebtedness” through financial literacy to the public, especially “borrowers.” To support this literacy, Fintech P2P Lending organizers are required to carry out financial socialization and education activities based on Financial Services Authority Regulation (POJK) No. 77/POJK.01/2016 as well as optimizing the implementation of the basic principles of Fintech P2P Lending, such as transparency of products and offering methods, prevention of excessive borrowing, and the application of the principle of good faith. Utility: This research is expected to support literacy to the community in choosing a good financing institution. To support this literacy, Fintech P2P Lending organizers are required to carry out financial socialization and education activities. Novelty/Original: In contrast to previous research, this research focuses on the phenomenon of over-indebtedness in illegal Fintech P2P Lending during the COVID-19 pandemic, which until now has not been specifically studied.